Larval surveys reveal breeding site preferences of malaria vector Anopheles spp. in Zanzibar City - Kaeden K. Hill; Dickson Kobe; Narriman S. Jiddawi; Jonathan R. Walz; Katharina Kreppel (PLoS ONE, 2025)
In Zanzibar City - the capital of the Zanzibar archipelago in Tanzania - the incidence of malaria has decreased over the past few decades due to standardized treatment protocols and public health interventions targeting adult mosquitoes. However, the incidence remains between 1–2%, and case numbers have increased over the past few years because of a continued influx of Plasmodium spp. from other malaria-endemic areas (including mainland Tanzania). Larviciding is a powerful tool to target mosquito populations and reduce the incidence of malaria. However, larvicidal strategies rely on knowledge of the breeding patterns of malaria vector mosquitoes. In Zanzibar City, no larval surveys have been done in the last few years. Our aim was to characterize Anopheles spp. breeding sites in Zanzibar City during the rainy season. We first conducted systematic larval surveys across 16 semi-permanent/permanent water bodies and 30 temporary water bodies. Then, we used principal component analysis and logistic regression to model the effects of physical/chemical parameters and rainfall on Anopheles presence. We found that Anopheles spp. prefer concrete, semi-permanent breeding sites with high levels of dissolved oxygen but are also found in natural sites after heavy rains. Our logistic regression model successfully predicted the presence of Anopheles larvae, achieving a positive predictive power of 65.7% and a negative predictive power of 88.8%. The data from our study suggest that Anopheles spp. have not yet adapted to more polluted breeding sites in Zanzibar City (as they have in some mainland locations). These results can inform targeted larvicidal strategies in Zanzibar City.